METODE ISTINB?T AL-TAR?QAH AL-ISTINB?T AL-J?MIAH BAINA TAR?QAH AL-LAFZIYYAH WA MANAWIYAH DALAM MAQ?SID AL-SYAR?AH MAZHAB SYATIBY - Samsidar Samsidar (Fakultas Syariah dan Hukum Islam Institut Agama Islam Negeri Bone, 2017)
Abstract: The Shari'a of Islamic conveyed in the Qur'an and As-Sunnah in a comprehensive way requires a thorough and sustained scientific study and study. Inside both lafaz are bright and not bright meaning. Meanwhile, the texts of the Qur'an and Sunnah have ceased, while time continues with a number of events and problems that continue to come and go and stop. Therefore, serious efforts are needed to solve problems that are not expressly indicated by the texts. Alquran and Assunnah, is a source of Islamic law, either in the form of orders or prohibitions. In fact the Qur'an and Assunnah are arranged in Arabic. Then of course one way to understand the purpose of the Shari'a in it is the understanding of the language used is the Shari'a with all the ins and outs, in this case the Arabic language, knowledge of Arabic still must be equipped with the ability to understand the meaning of a lafazh nash, istinb?t al- tar?qah al-istinb?t al-j?miah baina tar?qah al-lafziyyah wa manawiyah in maq?sid al-syar?ah mazhab syatibyKata Kunci: Istinbat, Tar?qah AL-Lafziyyah wa Manawiyah